Kontribusi Daya Ledak Tungkai Dan Kecepatan Lari Dengan Kemampuan Lompat Jauh - Hasruddin Hasruddin (STKIP Paris Barantai, 2019)
This research is a type of descriptive research. Formulation of the problem in this study: Is there a contribution of explosive limb power with long jump capability, Is there an agreement on running speed with the students' long jump ability, Is there a contribution of explosive limb power and relaxed running which is shared together with the long jump ability. Explosion of the leg with the long jump ability, to find out if there is support for running speed with the ability of the long jump, to find out if there is an estimate of the explosive power of the limbs and the runs running together with the long jump capability. The population of all male students of Junior High School in SMP Negeri 3 Kotabaru Regency, 30 male students of SMP Negeri 3 Kotabaru Regency were sampled. Techniques for determining samples randomly by drawing. Data analysis techniques with descriptive analysis and inferential analysis through the SPSS 22.00 program with a significant level of 5% or Î± = 0.05. The results of the study prove that: There is a contribution of explosive limb power with a long jump capability of 43.9%. Some set the running speed with the ability of 35% far. There is a contribution of explosive limb strength and running speed together with a long jump capability of 47.5%. Keywords: leg explosive power, running speed, long jump.